2020
DOI: 10.26504/rs107
|View full text |Cite
|
Sign up to set email alerts
|

Income adequacy in retirement: Evidence from the Irish longitudinal study on ageing (TILDA)

Abstract: The mission of the Economic and Social Research Institute is to advance evidencebased policymaking that supports economic sustainability and social progress in Ireland. ESRI researchers apply the highest standards of academic excellence to challenges facing policymakers, focusing on 12 areas of critical importance to 21st Century Ireland. The Institute was founded in 1960 by a group of senior civil servants led by Dr T.K. Whitaker, who identified the need for independent and in-depth research analysis to provi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(16 citation statements)
references
References 22 publications
(32 reference statements)
1
15
0
Order By: Relevance
“…Much of the existing work in this area in the Irish context has focused on the extent to which those who are either already retired or very close to retirement are at risk of inadequate incomes in retirement (Beirne et al, 2020;Bercholz et al, 2019;Nivakoski, 2014;Nivakoski and Barrett, 2019). While assessments of retirement income adequacy are sensitive to the measure of adequacy adopted, and the definition of retirement income, the most recent Irish estimates suggest that approximately 9 per cent of those approaching the state pension age (SPA) over the period 2022-2027 would be at risk of poverty using the 60 per cent of median household disposable income poverty threshold, based on a definition of retirement income that includes state and supplementary pension income, as well as non-primary residence asset income (Beirne et al, 2020).…”
Section: Contextmentioning
confidence: 99%
See 3 more Smart Citations
“…Much of the existing work in this area in the Irish context has focused on the extent to which those who are either already retired or very close to retirement are at risk of inadequate incomes in retirement (Beirne et al, 2020;Bercholz et al, 2019;Nivakoski, 2014;Nivakoski and Barrett, 2019). While assessments of retirement income adequacy are sensitive to the measure of adequacy adopted, and the definition of retirement income, the most recent Irish estimates suggest that approximately 9 per cent of those approaching the state pension age (SPA) over the period 2022-2027 would be at risk of poverty using the 60 per cent of median household disposable income poverty threshold, based on a definition of retirement income that includes state and supplementary pension income, as well as non-primary residence asset income (Beirne et al, 2020).…”
Section: Contextmentioning
confidence: 99%
“…In this context, a recent study attempted to move beyond a single replacement rate to consider multiple indicators of retirement income adequacy, varying not only the definition of income, but also the benchmarks used to assess adequacy. Beirne et al (2020) used data from TILDA on the cohort of people born between 1955 and 1960 (and therefore expected to reach the state pension age over the period 2022-2027) to assess the adequacy of their projected income in retirement, using a variety of different benchmarks and definitions of retirement income. 5 The analysis found that assessments of income adequacy in retirement were very sensitive to the benchmark used.…”
Section: Retirement Income Adequacymentioning
confidence: 99%
See 2 more Smart Citations
“…27 In any case, Adam et al (2013) point out that double taxation is inherent to the taxation of wealth transfers, with CGT designed to serve an entirely different purpose (the taxation of the returns to saving) and no equivalent relief for income tax already paid on gifts or bequests. Exempting assets transferred at death from CGT creates an extremely strong incentive for older individuals to hold on to assets, such as investment properties, until death in order to bequest them tax-free to children, potentially contributing to lower levels of living standards and higher rates of poverty through retirement (Beirne et al, 2020).…”
Section: Other Cgt Reliefsmentioning
confidence: 99%